Educational technology for fatigue management related to antineoplastic chemotherapy - Marcela Maria de Melo Perdigão; Andrea Bezerra Rodrigues; Tayanne de Lima Magalhães; Fernanda Macedo Cartaxo Freitas; Lia Guedes Bravo; Patrícia Peres de Oliveira (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To construct and validate an educational technology (ET) on fatigue and non-pharmacological strategies for the management of this symptom in people with cancer undergoing outpatient antineoplastic chemotherapy. Method: This is a methodological study composed of three stages: 1) elaboration of the ET using the theoretical-methodological model of Doak, Doak and Root; 2) validation of content and appearance by seven nurses via the content validity index (CVI); and 3) a pilot test with 10 patients. Results: The ET "Knowing and coping with fatigue" contemplates the definition of fatigue, its causes and the interventions of physical exercise practice, sleep hygiene, energy conservation and behavioral intervention. The overall CVI obtained with the judges was 0.95. Conclusion: The ET presented content and appearance validity for health education regarding fatigue related to antineoplastic chemotherapy in outpatient cancer patients.